STUDI KRITIS PERAN KOMITE SEKOLAH DI MTS NURUL IKHSAN - Hardiansyah, Hardiansyah (Jurnal Paedagogy, 2020)
The purpose of this study was to identify, describe and analyze the role of the school committee in (1) The process of preparing a school income and expenditure budget plan (RAPBS) at MTs Nurul Ikhsan Batukliang, (2) How to obtain financial support and allocation of education costs at MTs Nurul Ikhsan Batukliang , and (3) Supervision and evaluation of tuition fees at MTs Nurul Ikhsan Batukliang. The research method used is a qualitative method with data analysis techniques consisting of three stages, namely data reduction, data presentation and verification or conclusion. The research results show that the performance of the school committee, especially in education financing at MTs Nurul Ikhsan Batukliang in accordance with its duties and functions, namely as advisory. agency (giver of considerations), supporting agency (supporting educational service activities), controlling agency (controller activities) and mediator (liaison) have made a positive contribution to the progress of the school. The progress that has been achieved includes physical and non-physical infrastructure. Good cooperation between the school and the committee can be seen from the solidarity in the preparation of the RAPBS so that all planned programs receive financial support from the government, student guardians and the private sector.